Risk of malignancy associated with cytomorphology subtypes in the salivary gland neoplasm of uncertain malignant potential (SUMP) category in the Milan System: A bi‐institutional study. Issue 6 (22nd May 2019) - Chowsilpa, Sayanan; An, Daniel; Lose, Holly; Huang, Xiao; Nayar, Ritu; Maleki, Zahra
Abstract : Background: Salivary gland neoplasm of uncertain malignant potential (SUMP) is a diagnostic category in the Milan System for Reporting Salivary Gland Cytopathology. The objective of this study was to assess the risk of neoplasm (RON) and the risk of malignancy (ROM) in SUMP cases by evaluating them based on their prominent cytomorphology. Methods: The pathology databases were searched for cases of fine‐needle aspiration–diagnosed SUMP at The Johns Hopkins Hospital and Northwestern University from 2013 to 2018. Only cytopathology cases diagnosed as SUMP that had available surgical follow‐up were included. Results: Sixty‐five patients with SUMP were identified, including 31 men and 34 women who ranged in age from 15 to 87 years (mean age, 55.2 years). Sixty‐five cases had histologic follow‐up, including 13 (20%) with basaloid features, 13 (20%) with oncocytic features, and 39 (60%) with unspecified features. No cases with clear cell features were found. Overall, the RON in the SUMP category was 95.4% (62 of 65 cases), and the ROM was 33.8% (22 of 65 cases). The RON in SUMPs with basaloid, oncocytic, and unspecified subtypes was 92.3%, 100%, and 94.9%, respectively, whereas the ROM was 38.5%, 7.7%, and 41%, respectively. The most common benign neoplasm was pleomorphic adenoma (23.1%), whereas mucoepidermoid carcinoma (9.2%) was the most common malignant neoplasm. Conclusions: This study shows that the ROM differs significantly based on cytomorphology subtypes, whereas the overall ROM is approximately the same as the target rate in the Milan System for Reporting Salivary Gland Cytopathology. Moreover, the RON remains high in the SUMP category among different cytomorphology subtypes. Adequate sampling, immunohistochemical staining, and familiarity with metaplastic and reactive changes may improve the diagnosis. Abstract : The risk of malignancy differs among cytomorphology subtypes of salivary gland neoplasms of uncertain malignant potential, and the risk of neoplasm remains high among all subtypes. The risk of neoplasm in salivary gland neoplasms of uncertain malignant potential with basaloid, oncocytic, and unspecified subtypes is 92.3%, 100%, and 94.9%, respectively, whereas the risk of malignancy was 38.5%, 7.7%, and 41%, respectively.